2016
DOI: 10.1115/1.4034927
|View full text |Cite|
|
Sign up to set email alerts
|

Review on Percolating and Neck-Based Underfills for Three-Dimensional Chip Stacks

Abstract: Heat dissipation from three-dimensional (3D) chip stacks can cause large thermal gradients due to the accumulation of dissipated heat and thermal interfaces from each integrated die. To reduce the overall thermal resistance and thereby the thermal gradients, this publication will provide an overview of several studies on the formation of sequential thermal underfills that result in percolation and quasi-areal thermal contacts between the filler particles in the composite material. The quasi-areal contacts are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Evaporative drying is a phenomenon present in many scientific and engineering processes, for example, design of new materials and structures, food preserving, and production of ceramics and paper. Recently, the self-assembly of nanoparticles induced by controlled evaporation of colloidal suspensions has attracted a lot of attention as a method for the fabrication of complex materials (Brunschwiler et al 2016;Hamon et al 2012;Boles et al 2016). Zurcher et al (2016) and Städler et al (2017) have been working on nanoparticle self-assembly by non-isothermal evaporation to create underfills with high thermal conductivity applied as materials for electronic packaging.…”
Section: Introductionmentioning
confidence: 99%
“…Evaporative drying is a phenomenon present in many scientific and engineering processes, for example, design of new materials and structures, food preserving, and production of ceramics and paper. Recently, the self-assembly of nanoparticles induced by controlled evaporation of colloidal suspensions has attracted a lot of attention as a method for the fabrication of complex materials (Brunschwiler et al 2016;Hamon et al 2012;Boles et al 2016). Zurcher et al (2016) and Städler et al (2017) have been working on nanoparticle self-assembly by non-isothermal evaporation to create underfills with high thermal conductivity applied as materials for electronic packaging.…”
Section: Introductionmentioning
confidence: 99%
“…Drying of colloidal suspensions is an interesting phenomenon observable in everyday life, for example, in the "coffee ring" [1,2] formed after drying of a coffee drop, and utilized commonly in industry, as with ink-jet printing [3]. This phenomenon has sparked the attention of researchers for a variety of applications such as the design of unique types of computer chips with high heat removal capacity [4][5][6] and innovative functional materials with better optical, magnetic, and electronic properties [7,8]. The accurate modeling of the drying of colloidal suspensions, a complex process involving coupled heat and mass transport and phase change, is very challenging.…”
Section: Introductionmentioning
confidence: 99%
“…PTSs are fabricated in a similar way omitting the third step described above. In the experimental study of [9], PTSs and NTSs are reported to increase the heat conduction two-to threefold, compared to state-of-the-art capillary thermal structures. However, an in-depth understanding of the mechanisms of colloidal liquid drying, nanoparticle deposition in the filler particle configuration, and the influence of necks on the heat conduction of NTS is still lacking and needs to be explored systematically.…”
Section: Introductionmentioning
confidence: 97%
“…Colloidal nanoparticle deposition on intended specific surfaces is also applied as ink-jet printing [5,6], or surface coating [7,8]. Recently, nanoparticle deposition has been used to enhance vertical heat conduction in innovative three-dimensional (3D) chip stacks to remove the heat generated in computer chips more efficiently [9][10][11]. In a 3D integrated chip stack, two or more layers of active electronic components are integrated vertically, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation